2012
DOI: 10.1371/journal.pone.0047460
|View full text |Cite
|
Sign up to set email alerts
|

Transcranial Red and Near Infrared Light Transmission in a Cadaveric Model

Abstract: Background and ObjectiveLow level light therapy has garnered significant interest within the past decade. The exact molecular mechanisms of how red and near infrared light result in physiologic modulation are not fully understood. Heme moieties and copper within cells are red and near infrared light photoreceptors that induce the mitochondrial respiratory chain component cytochrome C oxidase, resulting in a cascade linked to cytoprotection and cellular metabolism. The copper centers in cytochrome C oxidase hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
104
1
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 169 publications
(111 citation statements)
references
References 25 publications
4
104
1
2
Order By: Relevance
“…Similar sets of values have been recently reported for human cadaveric specimens. 16 Further, Detaboada and colleagues 10 estimated that there would be a power density decrease of more than 99% from the cortex to a depth of 18 mm in rats. Finally, in rats, Abdo and colleagues 1 noted significant attenuation of the NIr signal, with power reducing approximately 90% at approximately 1 mm deep from the cortex.…”
mentioning
confidence: 99%
“…Similar sets of values have been recently reported for human cadaveric specimens. 16 Further, Detaboada and colleagues 10 estimated that there would be a power density decrease of more than 99% from the cortex to a depth of 18 mm in rats. Finally, in rats, Abdo and colleagues 1 noted significant attenuation of the NIr signal, with power reducing approximately 90% at approximately 1 mm deep from the cortex.…”
mentioning
confidence: 99%
“…[11,12] Regarding the issue of skull penetration, Jagdeo et al had reported that near infrared measurably penetrated soft tissue, bone and brain parenchyma in the formalin preserved human cadaveric model. [13] With the transfrontal application one should keep in mind the variable size of the frontal sinus, the bone around the sinus is thicker, and not seldom a sinusitis affects severely affected chronic patients. A thick bone and fluid, however, decrease the speed and thus the power of the near-infrared laser light.…”
Section: Discussionmentioning
confidence: 99%
“…Also, the anticancer and anti-inflammatory properties of some substances commonly found in human food and beverages such as resveratrol and antocyanes in fresh fruit and vegetables, polyphenols in tea and coffee, compounds in herbs and spices such as curcumin, etc. have been thoroughly studied and confirmed (39,42,47,61). The other major factor, however, the positive attitude and genuine interest in life are often solely dependent on the attitude of the person.…”
Section: Let Time That Makes You Homely Make You Sagementioning
confidence: 93%